The Bergerie station of the Chemins de fer économiques des Charentes.... - Auteur inconnu (Wikimedia Commons, 1908)
Carte postale ancienne issue de Wikimedia Commons. Titre: The Bergerie station of the Chemins de fer économiques des Charentes. Postcard sent in 1908 (a). The Bergerie station of the Chemins de fer économiques des Charentes. Postcard sent in 1908. Nieul-le-Virouil once had a station. It was not located in the village but on the RN 137 at a place called 'La Bergerie', between Saint-Genis de Saintonge and Mirambeau.
Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; Patrimoine; Histoire Locale; Wikimedia Commons; gare